Simultaneous power generation and wastewater treatment by using air-cathode single chamber microbial fuel cell - Lim, Jia Han (2014)
Since the last decade, sustainable energy production and wastewater treatment are of top priority topics in the developing country such as Malaysia. Malaysia is a country that depends on natural gases and fossil fuels as energy sources which are all non-renewable energy sources. Besides, Palm oil mill effluent (POME) is a major wastewater generated in Malaysia during the production of palm oil products. It is highly polluting due to the high content of chemical oxygen demand (COD). Therefore, in order to produce energy and perform wastewater treatment simultaneously, biological wastewater treatment that used microbial fuel cell (MFC) is a promising technology. In this study, simultaneous power generation and wastewater treatment by using air-cathode single chamber MFC was carried out. A non-precious catalyst α-MnO2 was synthesized to be used for the oxygen reduction reaction (ORR) at the air cathode of the MFC in order to replace the commonly used precious catalyst, platinum (Pt.). The α-MnO2 was synthesised from KMnO4 in H2SO4 solution. It was characterized through X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), energy dispersive spectroscopy (EDS), and cyclic voltammetry (CV) analysis in order to examine its crystal structure, morphology, chemical composition and also its electrochemical activity in ORR. The XRD results confirmed the formation of α-MnO2 phase. The ORR activity from CV analysis indicated that the catalyst could be suitable for air cathode MFC. The air cathode single chamber MFC was set up with a 25mL anodic working volume in order to treat POME. Polyvinylpyrrolidone (PVP) was used as the binder for the catalyst to replace the commonly used Nafion solution. Besides, Polyacrylonitrile carbon felt (PACF) was used as electrode for the MFC system. Different catalyst loadings ranging from 0.10 to 0.20g were coated on the projected area of air cathode which is 7.07cm2 in order to study the effect of catalyst loading on the performance of the MFC based on the power generation and COD removal efficiency from POME. The result obtained showed that the power generation increased with the increase in catalyst loading. The results indicate that the ORR is still the limiting factor for the overall performance of the air cathode MFC. The maximum power density generated was 671.98mW/m3 and the highest COD removal efficiency was 21.7% when the catalyst loading was 0.20g on the projected area of air cathode. The α-MnO2 prepared from this study shows great potential to replace the conventional Pt catalyst in cathode.